2014
DOI: 10.1111/febs.12827
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the iron‐free true C‐terminal half of bovine lactoferrin produced by tryptic digestion and its functional significance in the gut

Abstract: Bovine lactoferrin, a 76-kDa glycoprotein (Ala1-Arg689) consists of two similar N-and C-terminal molecular halves with the ability to bind two Fe 3+ ions. The N-terminal half, designated as the N-lobe (Ala1-Arg341) and the C-terminal half designated as the C-lobe (Tyr342-Arg689) have similar iron-binding properties, but the resistant C-lobe prolongs the physiological role of bovine lactoferrin in the digestive tract. Here, we report the crystal structure of true C-lobe, which was produced by limited proteolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 47 publications
(70 reference statements)
2
25
0
Order By: Relevance
“…Interestingly, the C-terminal lobe has been recently reported to be resistant to trypsin digestion and retains antimicrobial activity through the conservation of a defined ironbinding site (Rastogi et al, 2014a;Rastogi et al, 2014b), which may be important when considering use of oral lactoferrin supplements and transit through the gastrointestinal tract.…”
Section: Lactoferrinmentioning
confidence: 99%
“…Interestingly, the C-terminal lobe has been recently reported to be resistant to trypsin digestion and retains antimicrobial activity through the conservation of a defined ironbinding site (Rastogi et al, 2014a;Rastogi et al, 2014b), which may be important when considering use of oral lactoferrin supplements and transit through the gastrointestinal tract.…”
Section: Lactoferrinmentioning
confidence: 99%
“…The previously reported procedure was used for the purification of lactoferrin . The preparation of C‐lobe was carried out using limited proteolysis with trypsin as described earlier . The purification of C‐lobe was also adopted from the previous studies …”
Section: Methodsmentioning
confidence: 99%
“…Although C‐lobe was also cloned and expressed but no structural studies were reported. Later on, C‐lobe was successfully produced by limited proteolysis using serine proteases . The first structure of a not so perfect C‐lobe consisting of residues, Tyr342–Ser676 and Leu681–Ala685 of bovine lactoferrin (BLF) (residues, Ala1–Arg689) produced by hydrolyzing lactoferrin using proteinase K (PK‐C‐lobe), was determined in iron saturated form (Holo‐PK‐C‐lobe) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is an extensive contribution. (Salunke et al, 1985;Banerjee et al, 1994Banerjee et al, , 1996Sankaranarayanan et al, 1996;Singh et al, 2001;Sharma et al, 2011;Rastogi et al, 2014) We need to include many areas like non-aqueous enzymology, enzyme promiscuity and moonlighting proteins in our syllabi and encourage people to work in these areas. The first one offers an opportunity for biocatalyst-based synthesis of industrial and drug intermediates, agrochemicals and biosurfactants (Gupta, 1992;Halling, 1994;Carrea and Riva, 2000;Hudson et al, 2005).…”
Section: Applied Bio-catalysis and "Make In India" Programmentioning
confidence: 99%